Մարդկային գործոնի ակտիվացման դրսևորումն արդի ժամանակաշրջանում - Անահիտ Առաքելյան (ՀՀ ԳԱԱ հրատ.)
In the article the author turns to the conception «human factor», its structure ,the forms of expression of human factor, particularly individual’s social activity, as well as social responsibility and problems related to the social fairness and unfairness.
Keywords: Philosophy; Psychology; Religion